Baby Yoga Improves Weight of Baby 3-12 Month - Silvia Ari Agustina; Reni Merta Kusuma (Poltekkes Kemenkes Semarang, 2021)
Background: Emotional closeness is very important for physical growth, emotions and intelligence of babies. The benefit of doing Yoga is to create physical and mental health as well as creating a balance. Research on the effect of baby yoga on infant growth is still limited. The purpose of this study was to determine the effect of yoga on the baby's body weight and lengthMethods: The research method used is quasi-experimental design with the Pre-Post-test Control Group Design method. This study involved 36 samples of infants who had nutritional problems. Which were divided into 2 groups with 18 samples each. The treatment was carried out for 2 months, and 4 treatments were carried out monthly. The statistical test used is paired sample T-Test dan independent T-Test.Results: The statistical test result of paired sample T-Test for Baby Yoga treatment significantly affected the baby's weight and body length with p value = 0.000. The results of the Independent T-Test, the difference in body weight between the baby yoga group with growth and development stimulation was known to be p 0.05 (p = 0.012), there was a difference in weight gain between baby yoga and growth and development stimulation. However, for differences in body length difference test, showing a value of p 0.05 (p = 0.150), the results in body weight and body length difference between the treatment of baby yoga with growth and growth stimulation showed that there was no significant difference between the provision of baby yoga with growth and growth stimulation to increase body length.Conclusion: There is a weight difference between baby yoga treatment and growth stimulation, but no significant difference for body length.